The Good, The Bad, and the Indifferent: Lodging Homes in Hamilton, Ontario - Noble, Amanda (My University, 2016)
This research aims to explore the ways in which community-based mental health social workers assess the qualities of residential care facilities in order to make recommendations to their service users. The daily challenges of serving a marginalized population within the context of structural inequalities and neoliberalist service provision describe some of the contradictions that shape the work experiences of social workers. This research seeks to contribute to and further our understanding of critical social work practice, social justice, and structural oppression. In addressing the phenomenon of structural inequalities and neoliberalist service provision from the perspective of those affected, it will assist in a broader understanding of how social workers support service users to find supportive housing. Semi-structured interviews with community-based mental health social workers employed in Hamilton, Ontario were conducted and complement the existing literature on residential care facilities, the deterioration of the social welfare system, managerialism, and client-centeredness. This is an exploratory study as few previous research has been conducted with social workers in the context of lodging homes. Previous literature existed from the perspective of residents of lodging homes in Hamilton, Ontario. This research suggests that social workers are influenced by a complex number of phenomena in their daily work in order to make recommendations for supportive housing.
Keywords: lodging home; poverty; mental illness; social worker